Estimation of nitrate pollution sources and transformations in groundwater of an intensive livestock-agricultural area (Comarca Lagunera), combining major ions, stable isotopes and MixSIAR model. (15th January 2021) - Torres-Martínez, Juan Antonio; Mora, Abrahan; Mahlknecht, Jürgen; Daesslé, Luis W.; Cervantes-Avilés, Pabel A.; Ledesma-Ruiz, Rogelio
Abstract: The identification of nitrate (NO3 − ) sources and biogeochemical transformations is critical for understanding the different nitrogen (N) pathways, and thus, for controlling diffuse pollution in groundwater affected by livestock and agricultural activities. This study combines chemical data, including environmental isotopes (δ 2 HH2O, δ 18 OH2O, δ 15 NNO3, and δ 18 ONO3 ), with land use/land cover data and a Bayesian isotope mixing model, with the aim of reducing the uncertainty when estimating the contributions of different pollution sources. Sampling was taken from 53 groundwater sites in Comarca Lagunera, northern Mexico, during 2018. The results revealed that the NO3 − (as N) concentration ranged from 0.01 to 109 mg/L, with more than 32% of the sites exceeding the safe limit for drinking water quality established by the World Health Organization (10 mg/L). Moreover, according to the groundwater flow path, different biogeochemical transformations were observed throughout the study area: microbial nitrification was dominant in the groundwater recharge areas with elevated NO3 − concentrations; in the transition zones a mixing of different transformations, such as nitrification, denitrification, and/or volatilization, were identified, associated to moderate NO3 − concentrations; whereas in the discharge area the main process affecting NO3 − concentrations was denitrification, resulting in low NO3 − concentrations. The results of the MixSIAR isotope mixing model revealed that the application of manure from concentrated animal-feeding operations (∼48%) and urban sewage (∼43%) were the primary contributors of NO3 − pollution, whereas synthetic fertilizers (∼5%), soil organic nitrogen (∼4%), and atmospheric deposition played a less important role. Finally, an estimation of an uncertainty index (UI90) of the isotope mixing results indicated that the uncertainties associated with atmospheric deposition and NO3 − −fertilizers were the lowest (0.05 and 0.07, respectively), while those associated with manure and sewage were the highest (0.24 and 0.20, respectively). Graphical abstract: Image 1 Highlights: Sources, transformations and contributions of nitrate pollution in groundwater investigated. Thirty-two percent the samples exceeded the WHO limit for safe drinking water. Mainly the application of manure and sewage leaks drove the increase of nitrate concentration. Mixing process among evaporated soil water and recirculated water from irrigation identified. Different nitrate transformation processes in recharge, transition and discharge areas. Abstract : The combined approach estimated a number of nitrate pollution sources and transformation processes in groundwater, whereby manure and sewage leakages were the main drivers.